Amination of Polymeric Braid Structures to Improve Tendon Healing: An Experimental Comparison. Issue 1 (26th October 2022) - Peixoto, Tânia; Silva, Daniel; Rodrigues, Miguel; Neto, Miguel; Silva, Rui; Paiva, Maria C.; Grenho, Liliana; Fernandes, Maria Helena; Lopes, Maria A.
Abstract: Several polymers are researched for tendon repair as polyethylene terephthalate (PET) and polylactic acid (PLA). These are biocompatible and useful in scaffolding repair though with minimal success due to long‐term failure. There is a need to improve such scaffolds' design and physical–chemical nature. This work concerns surface functionalization of polymeric braids (PET and PLA) that fulfill the high mechanical demands of tissues such as tendons. The functionalization aims to incorporate amine groups in the braids' surface, improve cell adhesion, and consequently, the poor healing rate of these tissues and the biointegration of the braids. Two approaches are compared: the direct application of NH3 plasma and the surface grafting of EDA after O2 plasma activation. X‐ray photoelectron spectroscopy (XPS) shows that amine groups are effectively introduced onto the samples' surfaces. Besides, the plasma parameters chosen do not compromise the topography and tensile behavior of the braids. Resazurin assay and scanning electron microscopy show that the NH3 treatment improves cell–biomaterial interaction as improved cell adhesion and proliferation are observed. Both approaches are safe for biomedical applications. The NH3 plasma approach is more environmentally friendly, faster, and easier to scale‐up, showing potential for application in the final hybrid medical device. Abstract : Poly(ethylene terephthalate) (PET) and poly(lactic acid) (PLA) are polymers useful in tendon repair, though with minimal success. There is a need to improve such scaffolds' design and physical–chemical nature. The work concerns functionalization of PET/PLA braids to incorporate amine groups in the braids' surface, improve cell adhesion, and consequently, the poor healing rate of these tissues and the braids' biointegration.